Analysis Of Improving The Quality Of Education Services Based On Marketing Mix Theory (7PS) - Riska Fitriyanti; Nurlaila Nurlaila; Yulia Tri Samiha (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The competition between Islamic educational institutions and public schools compels private Islamic schools to continually enhance their educational services to meet their goals. This study examines how Al-Azhar Islamic Junior High School improves its educational services using the marketing mix theory, which includes seven elements: product, price, place, promotion, people, physical evidence, and process. A descriptive qualitative approach was employed, gathering data through interviews, observations, and documentation. Data analysis involved reduction, presentation, and concluding, with data validity ensured through triangulation. The findings show that the school effectively applies all seven marketing mix elements. The school adapts academic and non-academic programs to align with its mission, manages pricing independently, and uses its central location as a community attraction despite traffic congestion. Promotional strategies leverage social media and consumer satisfaction, while human resources are strengthened through quality recruitment and ongoing training. Physical evidence is reflected in the provision of distinctive, high-quality infrastructure. The learning process focuses on maintaining teaching quality. The study concludes that employing marketing mix theory is an effective strategy for improving educational services and competitiveness in the face of public school competition.